Digital discrimination detection in ridesharing services - Paiva, Raquel T. de; Cataldo, Wendy S.; Garcia, Ana Cristina B.; de Mello, Carlos E. (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2024: Anais do XIX Simpósio Brasileiro de Sistemas Colaborativos, 2024)
The introduction of technology has significantly transformed the urban transport industry, revealing social issues such as bias-driven trip cancellations. After a bibliographical review on how the topic is treated, we created an ontology and established the objective of analyzing digital discrimination, approaching it through the analysis of collective data, which can direct mechanisms to discourage discrimination in digital services. This study seeks to answer: RQ1: Is there evidence of digital discrimination in the shared transport service in the city of Rio de Janeiro? RQ2: Is it possible to identify the factors that lead to discrimination? RQ3: What are the key concepts related to detecting Digital Discrimination in a shared transport service?